A1 Financial and time costs of R&D governance and regulation in England and Wales: evidence from the SAFER 2 trial. Issue 11 (14th October 2011) - Hutchings, H; Lloyd, G; Snooks, H; Russell, I
Abstract : In response to a recent review targeted at reducing bureaucracy in medical research related to R&D governance and regulation, we collated our experiences from a multi centre trial in prehospital emergency care underway in England and Wales. We present recommendations about how to improve the system to avoid delays and spiralling costs. The SAFER 2 trial is an National Institute for Health Research (NIHR) Health Technology Assessment-funded cluster randomised controlled trial evaluating clinical and cost effectiveness of protocols for paramedics to refer older people for whom a 999 call has been made for a reported fall to community based care. We have encountered various issues relating to R&D processes, including: unclear guidelines about how R&D permissions work both within and across UK countries; inconsistencies in processes between sites; complex processes at global and local level; differing interpretations of the Attributing Revenue Costs of non-commercial research in the NHS (ARCO); multiple routes for reclaiming costs incurred by NHS Trusts through participating in research; difficulty of completing R&D permissions processes while uncertainty exists around the financial consequences of participation; and uncertainties related to ethical practice in research in emergency care. As a direct consequence of these issues we have encountered significant delays resulting in an application for an extension to the HTA for £420 000. We make a number of practical recommendations based on these experiences that could improve the R&D process. First, that the Department of Health (DoH) allocates sole responsibility for awarding research costs, excess treatment costs & service support costs to NIHR, thus removing at a stroke scope for interminable boundary disputes. Second, that the DoH issues more comprehensive standard operating procedures for Research Ethics Committees (REC), Comprehensive Local Research Networks and Trust R&D Departments, thus minimising inconsistent decision-making and duplication. Thirdly, that the National Research Ethics Service issues clear guidance to RECs on acceptable procedures for consenting in difficult circumstances, including emergency care and about when "opting out" is permissible.